Fattori antecedenti l’uso di un GIS: un’analisi nell’ambito della Pubblica Amministrazione - Picone, Luca (GEOmedia, 2009)
Antecedent factors of the use of a GIS: an empirical survey within italian local government To what extent are user perceptions taken into account for the GIS adoption process within Italian local governments? What are the main relationships within such an adoption process? A survey was carried out on 500 GIS users belonging to 350 Italian local governments. Typical issues of GIS adoption and implementation processes are not so different from the ones related to the redesign of business processes. Specifically, the focus moves from technical and technological issues to behavioral and organizational ones.